Depression and loneliness as mediators of purpose in life and quality of life in older adults : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Distance, New Zealand - Williams, Aleisha (Massey University, 2023)
Objective: Worldwide populations are aging. This can potentially be a valuable resource to both the older individual and their communities or an ethical burden. A key factor in determining the potential opportunities that arise from these extra years of life is well being. It is therefore important to understand determinants that foster healthy aging and well being through maximising functional ability and enabling engagement in things that matter to them. This study utilises Quality of Life as a holistic measure of a well-being in older age. The existing literature has provided some support for Purpose in Life, Loneliness, and Depression as being associated with each other; it also suggests they are important pre determinants of older adult Quality of Life. Based on previous literature it is possible the relationship between Purpose in Life and Quality of Life is partially mediated by Loneliness and Depression. Method: A structural equation model tested the longitudinal relationship between Purpose in Life and Quality of Life, and the potential parallel mediating effect of Loneliness and Depression, while controlling for Age, Gender, Marital Status, Social Support, Social Isolation and Socioeconomic Status. Sample: The analysis used observational survey-based secondary data obtained from three waves of the New Zealand Health, Work and Retirement Study. The participants represented older adults living in New Zealand, aged 55 years and over. Results: Correlational analysis found significant correlational relationships between the latent variables. Regression analysis found positive direct (B = .243) and indirect total effect (B = .227) relationships between Purpose in Life and Quality of Life. However, indirect effects were not significant when one mediator was controlled for. Conclusion: The current research supports prior findings that Purpose in Life predicts future Quality of Life in older adults and offers an important contribution towards future interventions aimed at older adult well-being. The mixed mediating results suggest further research is needed to understand the role of Loneliness and Depression as potential pathways between Purpose in Life and Quality of Life.
Keywords: purpose in life; loneliness; depression; quality of life; mediation; longitudinal; older adults; structural equation modelling; 520106 Psychology of ageing